PERANCANGAN MEDIA PROMOSI EVENT PUTRI LBC PADA LONDON BEAUTY CENTRE SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Hardyanti, Rurin Niken (Jurnal Art Nouveau, 2014)
Abstract: Putri LBC is one of event ever held by the London beauty Centre. London beauty Centreor better known as LBC is one of the leading beauty clinic which has been established for 16 years and has 46 branches all over in Indonesia. Putri LBC is a beauty contest that is intended for woman, especially teenagers.. This event is a means to establish a good relationship with the customers directly. But so far, Putri LBC has not promotional activities are well designed and just rely on word of mouth promotion to inform the event to the audience. this led to less customers know about the event and Putri LBC did not affect the increase in customers who visit the clinic LBC. The problem is that LBC is a clinic that has experienced yet visitors decreased gradually because more and more beauty clinics are popping up, especially in Surabaya, it takes some effort to maintain customer loyalty, one of which is to design a media campaign that is right for Putri LBC that can provide information to the public in order to increase brand loyalty Beauty clinic London Beauty Centre.